Perancangan Media Luar Ruang untuk Kampanye Pencegahan Covid-19 di Komunitas Perdesaan - Muhammad Badri (Lembaga penelitian dan pengabdian kepada masyrakat, 2020)
The Covid-19 pandemic encourages the vigilance of various elements of society to take precautions, including in rural areas. This community service activity aims to provide assistance in designing outdoor media for the Covid-19 prevention campaign in Desa Sungaibuluh, Singingi Hilir, Kuantan Singingi. This activity involves the subject of activity from determining the design concept, types of media, to production. The design process also pays attention to design principles, namely the selection of shapes, illustrations, colors, typography, and messages. This activity produced two types of media that were considered effective for the Covid-19 prevention campaign in rural areas, namely billboards and banners. Both of these media are installed in public places and crowds.